2021
DOI: 10.1038/s41393-021-00678-6
|View full text |Cite
|
Sign up to set email alerts
|

The neurological level of spinal cord injury and cardiovascular risk factors: a systematic review and meta-analysis

Abstract: Study design Systematic review and meta-analysis. Objective To determine the difference in cardiovascular risk factors (blood pressure, lipid profile, and markers of glucose metabolism and inflammation) according to the neurological level of spinal cord injury (SCI). Methods We searched 5 electronic databases from inception until July 4, 2020. Data were extracted by two independent reviewers using a pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…Furthermore, in individuals with chronic SCI, the level of injury was suggested as potential non-modifiable cardiovascular risk factor, implying higher risks in individuals with tetraplegia. 10 However, a recent study reported that adding characteristics of the SCI (injury level and completeness) did not improve the performance of FRS in SCI, therefore, this merits to be explored in future studies with longer follow-up. 37 Finally, future research should also focus on validating or developing other body indices that better reflect adiposity in this group.…”
Section: Clinical Implications and Future Outlookmentioning
confidence: 98%
See 3 more Smart Citations
“…Furthermore, in individuals with chronic SCI, the level of injury was suggested as potential non-modifiable cardiovascular risk factor, implying higher risks in individuals with tetraplegia. 10 However, a recent study reported that adding characteristics of the SCI (injury level and completeness) did not improve the performance of FRS in SCI, therefore, this merits to be explored in future studies with longer follow-up. 37 Finally, future research should also focus on validating or developing other body indices that better reflect adiposity in this group.…”
Section: Clinical Implications and Future Outlookmentioning
confidence: 98%
“…Individuals with SCI experience these more frequently and with earlier disease onset, 1‐3 which is attributed to the accumulation of cardiometabolic risk factors, namely hyperlipidemia, hypertension, glucose intolerance, and obesity, 7,8 which arise due to the impairments in the metabolic milieu, which occurs a few days or weeks following the injury and worsen thereafter. Specifically, the impairment of autonomic nervous system coupled with changes in body composition and limitations in physical activity can lead to derangements in lipid and glucose metabolism, and blood pressure dysregulation 9‐13 . Despite the available evidence regarding the higher CVD risk in chronic SCI, 2,7,14 the early changes in CMD risk factors following the injury have been insufficiently explored 15‐18 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These cardiovascular disorders are important because they cause high morbidity and mortality in SCI patients. The prevalence of death from cardiovascular complications reaches up to 30 percent of deaths in SCI patients (3,34).…”
Section: Introductionmentioning
confidence: 99%